Level of use and public awareness in consumption of traditional medicines in work area of Health Center Gombong I - Naelaz Zukhruf Wakhidatul Kiromah; Tri Cahyani Widiastuti (Universitas 'Aisyiyah Yogyakarta, 2020)
Indonesia has 20,000 types of plants where 300 species have been used as traditional medicines. The use of traditional medicine as an alternative treatment in Indonesia that has been used by both rural and urban communities. The use of traditional medicine is considered safer than modern medicine. The purpose of this study was to identify the level of use of traditional medicine and public awareness in the use of traditional medicine in work area of Health Center Gombong 1 which consists of 5 villages. This research is a non-experimental and descriptive research that uses a questionnaire. Respondents who participated in this study were 140 people. The characteristics of respondents who participated in this study were the majority of men (50,71%), last educated of elementary school (41,43%), as housewives (27,86%). The majority of people in work area of Health Center Gombong choose treatment with modern medicine (64,29%). In addition there are 35,71% using traditional medicine and the majority use rhizome species (46%) for the treatment of minor ailments. In this study also showed that the majority of people do not know the safety of traditional medicines (50%) due to lack of information so that information is needed on the benefits and safety and the use of good and appropriate traditional medicines.